Relationship between knowledge of orthodontic treatment risks and interest in using fixed orthodontic appliances among Hasanuddin University students: Hubungan pengetahuan risiko perawatan ortodonti dengan minat penggunaan peranti ortodonti cekat pada mahasiswa Universitas Hasanuddin - Habar, Eddy Heriyanto; Mahardika, Ariva; Pawinru, Ardiansyah S. (Makassar Dental Journal PDGI Makassar, 2024)
Malocclusion can affect physical, social and psychological well-being and self-esteem. Therefore, interest in the need for ortho-dontic treatment is increasing to improve the appearance, function of teeth, psychological well-being and quality of life of a person. However, orthodontic treatment carries some risks. This study aims to determine the relationship between knowledge of treatment risks and interest in using fixed orthodontic appliance. This type of research is analytical observational with a cross-sectional re-search design. The subjects of this research were 99 Hasanuddin University students from the class of 2021 and 2022. It is con-cluded that the results obtained are that the two variables have a unidirectional relationship, but it is very weak and not significant.